DETERMINAN YIELD OBLIGASI PEMERINTAH DITINJAU DARI VARIABEL MONETER - Dara Mutia Fikhriani; Chenny Seftarita; Nita Faiziah; Fitrah Afandi (Fakultas Ekonomi dan Bisnis UNSYIAH, 2022)
AbstracGovernment fiscal policy has a big impact on the economy. One of the government's strategies is to optimize state finances by increasing efficiency in the management of state property and sources of state financing. The purpose of this survey is to: BI rate and inflation can influence government bond yields. The study relied on secondary data in the form of time series monthly obtained from various government agencies. For the period 2012-2021, Autoregressive Distributed Lag (ARDL) regression was used as the estimation method. According to the findings, the BI rate has a significant positive impact on bonds yields in both the long and short term, while inflation variables have a positive but not significant effect in the long term. The central bank, as the issuer of interest rates, and the government, as the keeper of inflation stability, are expected to keep interest rates low and inflation stable, so that government bond prices rise and attract investors, while also keeping rupiah value stable, so that foreign investors are interested in investing in the Indonesian bond market.Keyword: Monetary Policy, BI rate, Inflation, Yield Bond, Government Bond